Predictors of short‐term outcomes of burn in a newly established burn centre in Iran - Zakiyeh Jafaryparvar; Masoomeh Adib; Atefeh Ghanbari; Mohammad Ali Yazdanipour (Wiley, 2021)
Abstract Aim This study aimed to determine the predictors of hospital stay and mortality in patients with burns. Design This is a cross‐sectional, retrospective study. Methods This study was performed on 626 medical records in Velayat Subspecialty Burn and Plastic Surgery Center in Rasht, Iran, during 2008-2013. Results Men comprised 78.4% of the study population. Overall, 50.2% of the participants lived in rural areas, and 72.5% were married. The majority of burns occurred at home (49.5%), and thermal factor (87.4%) was the major cause of burn injuries. Also, 6.9% of the patients died after burns. The mean length of hospital stay was 12.62 ± 13 days. Age (OR = 1.07), total body surface area (TBSA%) (OR = 1.12) and length of ICU stay (OR = 1.06) were the strongest predictors of mortality. Gender (IRR = 0.85), TBSA% (IRR = 1.01), location of burn (IRR = 1.1), skin graft (IRR = 2.12), length of ICU stay (IRR = 1.04), re‐hospitalization (IRR = 1.77) and burn degree (IRR = 1.09) were the predictors of the length of hospital stay. Conclusion BSA is still an important predictor of mortality and length of hospital stay, as the most important short‐term outcomes of burns.